The potential risk of ventilator-induced lung injury from five different PEEP titration techniques in ARDS - Sutherasan, Yuda; Songsomboon, Chayanon; Gulapa, Kridsanai; Junhasavasdikul, Detajin; Theerawit, Pongdhep (Frontiers in Medicine, 2025)
IntroductionThe optimal positive end-expiratory pressure (PEEP) in acute respiratory distress syndrome (ARDS) remains uncertain. This study compared the PEEP levels using five distinct titration methods to assess potential ventilator-induced lung injury (VILI).MethodsThis study included 21 patients with moderate to severe ARDS who were monitored using esophageal balloon manometry and electrical impedance tomography (EIT). A recruitment maneuver followed by decremental PEEP titration was performed. Optimal PEEP (OP) was assessed using five criteria: highest respiratory system compliance (CRS), highest lung compliance (CL), end-expiratory transpulmonary pressure (Ptp_ee_direct) ≥ 0 cm H2O, elastance-derived end-inspiratory transpulmonary pressure (Ptp_ei_derived) ≤ 25 cm H2O, and EIT-based analysis balancing the degree of overdistention and lung collapse.ResultsSignificant differences in OP were observed across the methods (p = 0.001): CRS 8.0 cmH₂O (8.0,13.9); CL 9.8 cmH₂O (8.0,14.0); Ptp_ee_direct ≥ 0 cmH₂O 14.0 cm H₂O (11.9,17.9); Ptp_ei_derived ≤ 25 cmH₂O 12.0 cmH₂O (10.0,13.9); EIT balancing the degree of overdistention and lung collapse 13.01 cmH₂O (9.88,14.78). The OP guided by Ptp_ee_direct of ≥ 0 cm H2O is significantly higher than OP by the highest CRS (p = 0.001) and the highest CL (p = 0.002), and met the overdistension criteria, namely plateau pressure > 30 cm H2O and the highest percentage of overdistension by EIT. The PEEP guided by CRS had a higher potential risk of lung collapse, reflected by the negative value of Ptp_ee_direct and a higher percentage of lung collapse by EIT.ConclusionTranspulmonary pressure-guided PEEP titration yielded higher PEEP levels, while CRS-guided PEEP was lower and associated with a higher risk of collapse. Overdistension and collapse varied with the chosen PEEP method. In patients with moderate to severe ARDS, OP can vary depending on the method of assessment.